Faktor Penentu Kejadian Stunting pada Anak Balita di Wilayah Kerja Puskesmas Alak Kota Kupang - Welmince Ina Lobo; Anna Henny Talahatu; Rut Rosina Riwu (Media Kesehatan Masyarakat, 2019)
Stunting is a chronic nutritional problem that can give an idea of the failure of growth accumulated since before and after birth resulting from inadequate intake of nutrients. Alak Health Center has 137 children stunting toddlers, and the working area of Alak Health Center is one of the villages that are included in the priorities of the stunting treatment in Kupang city. This research aims to determine of stunting incidence in children in the working area of Alak health center of Kupang City. This type of research is analytical surveys with a case-control research draft. The number of Samples of 110 infants selected systematic random sampling. Data retrieval is conducted using field measurements and structured interviews using questionnaires. Data analysis was conducted with a Chi-square test (bivariable) and double logistic regression (multivariable) with α = 0.05. The result of bivariable analysis with a value of P < 0.25 is the level of maternal education, parental income level, maternal nutritional knowledge level, large family, feeding practice, the practice of hygiene and environmental sanitation, care of children in pain, foster pattern, energy sufficiency level, and protein adequacy rate. The results of multivariable analyses showed the practice of environmental hygiene and sanitation, protein adequacy levels, and maternal nutritional knowledge level. It was concluded that the determining factor of stunting in children of toddlers in the workplace of health centers Alak Kupang City is the most dominant is the practice of environmental Hygiene and sanitation (OR = 7,986), the level of protein adequacy (OR = 4,132) and the level of maternal nutritional knowledge (OR = 2,553).